Implementación de un sistema domótico de seguridad y control mediante IOT aplicado a un laboratorio. - Moreno Chuqui, Washington Rafael (2023)
This project focuses on the development of a secure access control system based on the Internet of Things (IoT) with the objective of improving the operation of the Additive and Subtractive Manufacturing Laboratory. The conception of this system focuses on two fundamental components: access management to the laboratory and control through IoT. One of the essential pillars is related to the management of people entering the laboratory. To this end, the implementation of a system that enables access through facial recognition, card reading or RFID key fobs, as well as through IoT via the Telegram platform, has been proposed. In addition, the aim is to keep a visual record of the people who enter the laboratory. On the other hand, it highlights the importance of light control, which translates into the ability to automatically turn lights on and off. This function is especially useful for preventing energy waste, as well as for controlling power outlets, since 3D printers are connected that continue to consume energy even when they are not in use. To determine the system configuration, an analysis of various microcontrollers that could be considered is carried out. In addition, sizing criteria are applied to each of the key aspects of the system. The overall evaluation of the system yields results with a success rate of over 90% in each of the aspects evaluated. In addition to its current performance, the system has the capacity to be improved and upgraded, since programmable microcontrollers are used.